Power Quality (PQ) Improvements Using Different Types of Devices in Power Systems to Develop Smoothened Power Supply - T. C. Manjunath; Rajashekher Koyyeda, Ravi Rayappa (Journal of Power Electronics and Devices, 2021)
Power Quality (PQ) improvements using different types of devices in power systems to develop smoothened power supply are presented in brief in the form of an exhaustive literature review, w.r.t. the work carried out by various authors in this field. In this 1st part of the research paper, a brief review of the power quality improvements in power electronics-based equipment – an insight into the problem is presented in a nutshell. Here, how the power can be improved, i.e., the quality of the power which deteriorates due to the continuous switching on & off of the different types of loads is presented concisely. The paper serves as a shot in the arm for the researchers who want to work in the field of power electronics. The latter part of the matter presented in this paper is the work of another one, i.e., the second part & is presented next. In this 2nd part of the research paper, a brief review of the power quality improvements in power electronics-based equipment – an insight into the problem is presented in a nutshell. Here, how the power can be improved, i.e., the quality of the power which deteriorates due to the continuous switching on & off of the different types of loads is presented concisely. The paper serves as a shot in the arm for the researchers who want to work in the field of power electronics. The 2nd part of the paper is presented in this context here.